PROLONGED THERAPY WET FORM OF AGE-RELATED MACULAR DEGENERATION BY THE INTRODUCTION OF BEVACIZUMAB ON THE VISCOUS MEDIA IN SUBTENON SPACE (PRELIMINARY RESULTS) - A. N. Epihin; R. V. Gaibaryan; U. N. Epihina (Медицинский вестник Юга России, 2014)
Purpose: To evaluate the clinical clinical application subtenon administration of bevacizumab on the viscous media with the purpose of strengthening and prolong of therapeutic effect in the treatment of wet form of age-related macular degeneration (AMD).Materials and Methods: The study included 6 patients (6 eyes) with the wet form of AMD, who underwent the introduction of bevacizumab at a dose of 5 mg (0.2 ml) into the back subtenon space for viscous media – hydroxypropylmethylcellulose (the patent application on the invention of the Russian Federation №2013105697 from 11.02.2013). All patients underwent visometry, biomicroscopy, ophthalmoscopy, fundus photographic recording, optical coherence tomography and fluorescein angiography. The follow-up 3 months.Results: The mean values of visual acuity with correction improved after treatment (from 0.06 to 0.2). Central retinal thickness average decreased after treatment all patients (363.5 μm to 309 μm). Also, we have seen a significant decrease in transsudativnyh processes in the retina in all patients and reducing the suretinal of a neovascular membrane into 1.2 times, that speaks about supperession of activity choroidal neovascularization. The effect was observed throughout the period of observation.Summary: Subtenon introduction of bevacizumab is safe and has a positive effect in wet AMD, and its application to a viscous mediа has a prolonged effect.